Perceptions of early childhood and elementary school teacher's about the impacts of the pandemic on their personal and professional routines - Santos, Camila Elidia Messias dos [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Silva, Nilson Rogerio da [UNESP]; Capellini, Vera Lucia Messias Fialho [UNESP] (Univ Federal Santa Maria, 2024)
The present study aimed to describe how early childhood and elementary school teacher's perceived and experienced the impacts of the pandemic in their personal and professional daily lives, as well as to compare both levels of education. This is a descriptive research, survey type, with 74 teachers, 34 from early childhood and 40 from elementary school, living in a countryside city in the state of S & atilde;o Paulo, which was carried out through an electronic form composed by: a) a questionnaire of sociodemographic and labor data, and b) an inventory of my profession in the pandemic. The data were organized by relative frequency and statistically analyzed. The results pointed out impacts of the pandemic in both segments and contexts analyzed, mainly related to the lack of technological equipment, both at school and by the families, besides the fear of contracting covid when returning to classroom. Therefore, the formulation of new working conditions for teachers is needed, considering the physical infrastructure, collaborative work and continuing education based on digital technological resources.
Keywords: Teacher; Remote Learning; Covid-19